Validation of a novel direct-injection chemiluminescence-based method for N-nitrosamine analysis in advanced-treated recycled water, drinking water, and wastewater. Issue 4 (27th February 2020) - Roback, Shannon L.; Kodamatani, Hitoshi; Fujioka, Takahiro; Plumlee, Megan H.
Abstract : A novel method for N -nitrosamines analysis requiring significantly less time, labor and cost than standard methods is shown to have acceptable performance in multiple water matrices and yield similar results. Abstract : N -Nitrosamines are water contaminants of public health concern due to their carcinogenicity at low concentrations. These compounds can form in wastewater and drinking water when chloramination is utilized for disinfection. Monitoring of N -nitrosamines by current analytical techniques is difficult, time-consuming, and expensive. Therefore, a simpler method developed in 2009 utilizing high-performance liquid chromatography (HPLC) with detection by photochemical reaction (PR) and chemiluminescence (CL) and requiring almost no sample preparation (no extraction) was tested and validated in the present study for potable reuse applications. The method accuracy, precision, and detection limits were determined using standard methods. Accuracy and precision met U.S. EPA standard method requirements for four N -nitrosamines [ N -nitrosodimethylamine (NDMA), N -nitrosopyrrolidine, N -nitrosomorpholine, and N -nitrosomethylethylamine] in the four recycled water matrices tested: (1) secondary wastewater effluent, (2) microfiltered wastewater effluent, (3) advanced purified water (after reverse osmosis and ultraviolet/advanced oxidation), and (4) ultrapure (Milli-Q) water. Method reporting (MRL) and detection limits (MDL) were similar or lower (1.2 ng L −1 MRL for NDMA) than those documented for conventional N -nitrosamine analytical methods (typically 2 ng L −1 MRL for NDMA). Split samples were collected from an advanced water purification facility weekly over six months and less frequently from four additional water utilities and analyzed by the HPLC-PR-CL method and conventional methods employed by the utility's laboratory (liquid- or solid-phase extraction/gas chromatography/dual mass spectrometry). The relative percent difference for all non-wastewater samples was low (6–18%) with wastewater effluent samples having a higher difference (11–53%).